Evolution of Multi-Resistance to Vancomycin, Daptomycin, and Linezolid in Methicillin-Resistant Staphylococcus aureus Causing Persistent Bacteremia - Chen, Chih-Jung; Huang, Yhu-Chering; Shie, Shian-Sen (Frontiers in Microbiology, 2020)
The genomic evolution in vivo in persistent infection was critical information for understanding how methicillin-resistant Staphylococcus aureus (MRSA) was adapted to host environments with high antibiotic selective pressure. Thirty-two successive MRSA blood isolates with incremental non-susceptibility to vancomycin (VISA), daptomycin (DRSA) and/or linezolid (LRSA) were isolated from a patient failing multiple courses of antimicrobial therapy during 1,356 days of bacteremia. Whole genome sequencing (WGS) for all consecutive isolates were conducted to characterize the evolutionary pathways, resistance-associated mutations and their temporal relationship with antimicrobial treatment. The WGS-based phylogeny categorized the isogenic strains into three major clades, I (22 isolates), II (7 isolates) and III (3 isolates), respectively, harboring a median (range) of 7 (1-30), 62 (53-65) and 118 (100-130) non-synonymous mutations when compared to the very first isolate. Clade I strains were further grouped into early and late sub-clades, which respectively shared the most recent common ancestor with clade III strains at day 393.7 and clade II strain at day 662.5. Clade I and clade III strains were characterized respectively with high rates of VISA (9/22, 40.9%) and VISA-and-DRSA phenotype (2/3, 66.7%). Linezolid-resistance including VISA-DRSA-and-LRSA phenotype was exclusively identified in clade II strains after 8 courses of linezolid treatment. The LRSA displayed a small colony variant phenotype and were associated with G2576T mutations in domain V region of 23S rRNA. Substantial loss of mobile elements or alleles mediating resistance or virulence were identified during the evolution of multi-resistance. However, the gene loss was might not be correlated to the development of VISA, DRSA or LRSA phenotype. In conclusion, MRSA in persistent bacteremia was adapted to harsh host environment through multiple pathways involving both resistance-associated mutations and extensive gene loss.